1987
DOI: 10.1136/bmj.295.6599.623
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and risk of myocardial infarction and death in the adult population of eastern Finland.

Abstract: Body mass index (weight (kg) divided by height squared (m2)) and its association with the risk of myocardial infarction and death from all causes were studied prospectively in a randomly selected population sample in eastern Finland aged 30-59 at outset in 1972. The study population consisted of 3786 men and 4120 women. The participation rate in the survey in 1972 was over 90%. AlU deaths and admissions to hospital in the sample were obtained from the National Death Certificate and Hospital Discharge Register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…The linear relationship between BMI and the incidence of CVD and the J-shaped relationship between BMI and rate of mortality, which remained after the exclusion of probands with history of cancer, has been demonstrated in several cohorts. 2,5 Studies which have failed to demonstrate these relationships have generally been based on smaller cohorts 3,6 or shorter periods of follow-up. 3 With the exception of smoking, the prevalence of risk factors associated with the development of atherosclerosis increased in a statistically significant fashion with increasing body weight.…”
Section: Discussionmentioning
confidence: 99%
“…The linear relationship between BMI and the incidence of CVD and the J-shaped relationship between BMI and rate of mortality, which remained after the exclusion of probands with history of cancer, has been demonstrated in several cohorts. 2,5 Studies which have failed to demonstrate these relationships have generally been based on smaller cohorts 3,6 or shorter periods of follow-up. 3 With the exception of smoking, the prevalence of risk factors associated with the development of atherosclerosis increased in a statistically significant fashion with increasing body weight.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many prospective epidemiologic studies have evaluated the relationship between mortality and body mass index (BMI) (weight adjusted for height (kg/m 2 )), [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] which is commonly considered a surrogate for body fat. Study findings vary as to whether the relationship is best described as direct, J-or U-shaped, the latter two characterizations suggesting higher risks among both heavier and leaner individuals.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,7 ± 16 Even though obesity is an independent risk factor for the development of cardiovascular diseases 17 and several studies have demonstrated that visceral obesity in particular is strongly associated with the prevalence of coronary heart disease, 18 ± 20 whether BMI increases or not the thickness of the arterial wall is still a matter of debate. 1,2,7 ± 16 However, independent of the effect of obesity per se, it has been shown that reducing BMI by 5 would reduce the annual rate of carotid wall IMT progression by 0.133 mm per year.…”
Section: Introductionmentioning
confidence: 99%